A new species of casque-headed tree frog, genus aparasphenodon miranda-ribeiro (Amphibia: Anura: Hylidae), from the Atlantic rainforest of southern Bahia, Brazil - Pimenta, Bruno V.S.; Napoli, Marcelo F.; Haddad, Célio F.B. [UNESP] (Magnolia Press, 2009)
A new species of Aparasphenodon is described from patches of arboreal restinga within the Atlantic Forest Biome, in a region known as Baixo Sul in southern Bahia, northeastern Brazil. Aparasphenodon arapapa sp. nov. is promptly diagnosed from other Aparasphenodon mainly by having small size (male snout-vent length 57.4-58.1 mm), loreal region flattened and wide, and canthus rostralis rounded and poorly elevated. The wide and flattened snout resembles that found in Triprion and Diaglena, and possibly is a parallelism (homoplasy) related to the phragmotic behavior of casque-headed tree frogs to their microhabitat usage. The decision to allocate the new species in the genus Aparasphenodon is discussed in detail, as the single morphological synapomorphy of the genus, the presence of a prenasal bone, is insufficient to morphologically relate the new species to Aparasphenodon, Triprion, or Diaglena. © 2009 Magnolia Press.
Keywords: Aparasphenodon arapapa sp. nov.; Casque-headed tree frog; Hylinae; Taxonomy